Utilization of lime for stabilizing soft clay soil of high organic content - Sakr, M.; Shahin, Mohamed; Metwally, Y. (Springer, 2009)
This paper presents the results of geotechnical and mineralogical investigations on lime-treated soft clay soil from Idku City, Egypt, where high organic matters of about 14% exist. Lime was added in the order of 1, 3, 5 and 7% by weight and laboratory experiments after 7, 15, 30 and 60 days were conducted including the mineralogical and microstructural examinations, grain size analysis, plasticity limits, unconfined compressive tests, vane shear tests and oedometer tests. The results indicate that soft clay soil of high organic content of 14% can be stabilized satisfactorily with the addition of 7% lime. The results also demonstrate that the changes in the mineralogical contents and soil fabric of high organic lime-treated soft clay improve soil plasticity, strength and compressibility.